2019
DOI: 10.1021/acsomega.8b03476
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration Pathways of Gypsum and the Rehydration Mechanism of Soluble Anhydrite γ-CaSO4

Abstract: The dehydration products of gypsum under different temperature and water vapor pressure were investigated by thermodynamic theory. Additionally, the rehydration mechanism of soluble anhydrite was also studied by Monte Carlo (MC) simulations. The thermodynamic calculation results reveal that the dehydration mechanism of gypsum significantly depended on ambient temperature and water vapor pressure. In the high-temperature and low water vapor pressure region, gypsum dehydrates to form γ-CaSO 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…where n is the hydration number (19,36,37). Thus, the phase transformation is determined by the solubility of the different phases in this specific environment, and anhydrite has been proved to be a more stable phase and has lower solubility (19,20).…”
Section: Mechanisms Of Gypsum−anhydrite Phase Transformationmentioning
confidence: 99%
“…where n is the hydration number (19,36,37). Thus, the phase transformation is determined by the solubility of the different phases in this specific environment, and anhydrite has been proved to be a more stable phase and has lower solubility (19,20).…”
Section: Mechanisms Of Gypsum−anhydrite Phase Transformationmentioning
confidence: 99%
“…Thus, Stark and Wicht [2] in their compilation of the history of gypsum emphasized the importance of gypsum-based materials in fire protection in the Middle Ages in Europe. Although the thermal behavior of gypsum-based systems has been important for numerous technologies for thousands of years and has always been the subject of scientific activities, the mechanisms of the processes that take place during the exposure of gypsum to elevated temperatures are still controversial, as stated and reviewed, e.g., in [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Tang reported that the dehydration of the gypsum (atmospheric pressure) required a temperature of 400 K or greater. 37 The outcomes of the miniaturization using Ag-NPs are illustrated in Figure 5A. The two face areas in the CS-NRs, i.e., the long side face (length × short side [nm 2 ]) and the crosssection face (short side × short side [nm 2 ]) were calculated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, based upon the fact that the CS-NRs were fabricated in an aqueous medium, it is likely that they correspond to CaSO 4 ·2H 2 O (gypsum). Previously, Tang reported that the dehydration of the gypsum (atmospheric pressure) required a temperature of 400 K or greater …”
Section: Resultsmentioning
confidence: 99%